The Long-Term Effects of Breastfeeding on Child and Adolescent Mental Health: A Pregnancy Cohort Study Followed for 14 Years - Oddy, W.; Kendall, Garth; Li, Jianghong; Jacoby, P.; Robinson, M.; de Klerk, N.; Silburn, Sven; Zubrick, Stephen R; Landau, L.; Stanley, F. (Elsevier, 2009)
Objectives. To determine whether there was an independent effect of breastfeeding on child and adolescent mental health.Study design The Western Australian Pregnancy Cohort (Raine) Study recruited 2900 pregnant women and followed the live births for 14 years. Mental health status was assessed by the Child Behaviour Checklist (CBCL) at 2, 6, 8, 10, and 14 years. Maternal pregnancy, postnatal, and infant factors were tested in multivariable random effects models and generalized estimating equations to examine the effects of breastfeeding duration on mental health morbidity. Results. Breastfeeding for less than 6 months compared with 6 months or longer was an independent predictor of mental health problems through childhood and into adolescence. This relationship was supported by the random effects models (increase in total CBCL score: 1.45; 95% confidence interval 0.59, 2.30) and generalized estimating equation models (odds ratio for CBCL morbidity: 1.33; 95% confidence interval 1.09, 1.62) showing increased behavioral problems with shorter breastfeeding duration. Conclusion. A shorter duration of breastfeeding may be a predictor of adverse mental health outcomes throughout the developmental trajectory of childhood and early adolescence.